RESPONSE OF AFRICAN MARIGOLD TO DIFFERENT LEVELS OF RESPONSE OF AFRICAN MARIGOLD TO DIFFERENT LEVELS OF NITROGEN, PHOSPHORUS AND POTASSIUM UNDER MID-HILL CONDITIONS OF HIMACHAL PRADESH - GARGI SHARMA; M. L. VERMA; RAVINA PAWAR (The Bioscan, 2019)
The present investigation entitled “Effect of NPK on growth and yield of African marigold (Tagetes erecta L.) cv. Pusa Narangi Gainda” was carried out during the years 2017 and 2018. Study aimed to ascertain the effect of different levels of NPK on plant nutrient contents, their uptake, growth and yield of African marigold. The experiment was laid out in randomized block design with seven treatments comprising different levels of NPK with four replications. The maximum plant height and number of branches along with nutrient contents and uptake by plant was recorded under T7 (150 % recommended dose of NPK) and minimum was recorded under T1 (control). Treatment T6 (125 % recommended dose of NPK) proved to be the best in respect of flower yield and related parameters viz., first flower opening (63.70 days), flower duration (65.20 days), flower weight (7.17 g), flower diameter (6.95 cm) number of flowers per plant (25.83) and flower yield (133.43 q/ha).